Use of energy-storage equipped shunt compensator for frequency control - Nordlund, Mathias (My University, 2010)
The continuous growth of the electrical system, resulting in growing electric power demand, is putting great emphasis on system operation and control. These topics, together with system reliability and security, are becoming more and more of interest for the research community, in particular due to the recent trend towards restructuring and deregulation of the power supplies. It is under this scenario that Flexible AC Transmission Systems (FACTS) Controllers at transmission level and Custom Power Devices at distribution level represent both opportunities and challenges for an optimal use of the power systems. In particular, the Static Synchronous Compensator (STATCOM) is a key device for reinforcement of the stability in an AC power system and for mitigation of power quality phenomena. Although typically used for reactive power injection only, an upcoming idea today is to equip the STATCOM with an energy storage connected on the dc-link of the converter, thus also allowing short-term active power support to the power systems. This report focuses on the use of energy storage equipped STATCOM (also known under the name of E-STATCOM). As first, the current controller used in the compensator, which represents the heart of the control system, will be derived. Then, two additional control systems, in order to allow frequency control and power oscillation damping, will be derived and analyzed. To verify these control systems, a simple network will be used as a benchmark model in PSCAD/EMTDC and the results from the simulations will be analyzed. The obtained results on the stability improvement by aims of the E-STATCOM will be supported by analytical investigation. Furthermore, the need for active power support in the actual grid of Falbygdens Energi AB (FEAB) will be investigated. Finally, the impact of a controllable load, or “smart load”, on the dynamic performance of the investigated FEAB’s grid will be shown. In the investigated cases, the smart load will be controlled in order to meet the power balance between load and local production in case of islanding conditions. The obtained results show good dynamical performance of the system. By analyzing the results from the simulations it can be concluded that it is possible to temporary control the system frequency, given an adequate size of the energy storage. The size of the storage is of high importance, in particular in case of islanding operation. It will be shown that another important factor for a successful operation of the E-STATCOM is its location into the power system. The location of the compensator will impact the dynamic performance of the overall system as well as the energy storage ratings, in particular when used for power oscillation damping.
Keywords: Elkraftteknik; Electric power engineering